Significant decrease of the pathological stage I rectal carcinoma in the era of neoadjuvant therapy—A matter of concern. (December 2021) - Stelzner, Sigmar; Puffer, Erik; Zimmer, Joerg; Bleyl, Dorothea; Kittner, Thomas; Kuhn, Matthias; Jakob, Christiane; Witzigmann, Helmut; Mees, Soeren T.
Abstract: Background: Neoadjuvant treatment (nTx) for rectal cancer is commonly reserved for UICC stages II/III. Patients with stage I tumours (T1-2N0M0) are not candidates for nTx. The accuracy of treatment allocation depends on the precision of clinical staging, which is liable to understaging and overstaging. The study aimed at exploring changes in the proportion of stage pI patients with the introduction of nTx over a 26-year period. Materials and methods: All consecutive patients with histologically proven rectal cancer excluding carcinoma in situ were retrieved from a prospective database of our colorectal unit. Time periods were defined as per the use of nTx: baseline phase 1994–1997; implementation phase 1998–2005 and guideline phase 2006–2019. Trends over time regarding proportion of applied nTx and stage pI tumours were investigated. Results: Overall, 1468 patients met the inclusion criteria. There were no major differences in patients' characteristics, especially proportion of synchronous metastases (stage IV) over time. nTx was applied to 1.2% of patients without metastases in the baseline phase, to 29.6% in the implementation phase, and to 59.6% in the guideline phase (p < 0.001). Corresponding proportions for patients with stage pI were 31.0%, 26.3% and 14.2%, respectively (p < 0.001). Conclusion: With a stable proportion of stage IV carcinomas indicating no major changes in the patient cohorts, we could document a significant decrease of stage pI patients with increasing use of nTx. This trend clearly signals overtreatment caused by clinical T- and N-staging. More precise criteria are needed to better select patients with rectal cancer for nTx. Highlights: Indication for neoadjuvant therapy depends on accurate clinical staging. Overstaging of stage I tumours results in overtreatment and a 'yp' classification. In this series, proportion of UICC stage pI tumours decreased significantly over time. This trend correlated with a significant increase in the use of neoadjuvant therapy. Better criteria to select patients with rectal cancer for neoadjuvant treatment are needed.